In vivo demonstration of whole‐brain multislice multispoke parallel transmit radiofrequency pulse design in the small and large flip angle regimes at 7 Tesla. Issue 3 (23rd October 2016) - Gras, Vincent; Vignaud, Alexandre; Amadon, Alexis; Mauconduit, Franck; Le Bihan, Denis; Boulant, Nicolas
Abstract : Purpose: A multispoke specific absorption rate (SAR) ‐aware pulse design approach for homogeneous multiple‐slice small and large flip angle (FA) excitations with parallel transmission is proposed. The approach aims at optimizing in a slice‐specific manner the spokes locations and radiofrequency pulses. Methods: The problem is posed as a set of slice‐specific magnitude‐least‐squares problems, linked together by hardware and SAR constraints, and solved jointly using an active‐set algorithm. Average Hamiltonian theory is exploited in the large FA case to greatly reduce the computational burden. The approach is validated numerically by means of simulations and experimentally on two volunteers at 7 Tesla through application of a high‐resolution T 2 * ‐weighted brain imaging protocol. Results: The optimization of up to 1300 variables under 745 explicit constraints could be performed in less than 1 and 4 min for the small and large FA cases, respectively. The joint design proves valuable for SAR demanding protocols. Compared with the conventional circularly polarized mode, the designed pulses increased the signal by more than 40% in 70% of the voxels. Conclusion: The B 1 + inhomogeneity problem was mitigated efficiently in a multislice near whole‐brain coverage protocol in the small and large FA regimes using a rapid slice‐specific pulse design algorithm where the pulses were optimized jointly. Magn Reson Med 78:1009–1019, 2017. © 2016 International Society for Magnetic Resonance in Medicine.